Leveraging beneficial microbiome-immune interactions via probiotic use in cancer immunotherapy - Jani, Chinmay T.; Edwards, Kyle; Bhanushali, Charmi; Zheng, Xena; Salazar, Ana S.; Lopes, Gilberto; Watson, Dionysios C. (Frontiers in Immunology, 2025)
The gut microbiome is a critical regulator of systemic immunity and a major modulator of response to cancer immunotherapy with immune checkpoint inhibitors (ICIs). However, the clinical implementation of microbiome-inspired therapies that leverage these associations have proven challenging. Probiotics—live microorganisms thought to confer health benefits as part of food or food supplements—have gained increasing attention as readily testable, low-toxicity agents with potential of favorably influencing host–microbiome–immune interactions in the context of cancer immunotherapy. In this review, we critically evaluate the growing body of evidence supporting the role of probiotics in enhancing ICI efficacy and summarize published and ongoing clinical trials formally testing their role as adjuncts to cancer immunotherapy. Probiotics have been shown in preclinical murine models to exert immunomodulatory effects, including activation and maturation of dendritic cells, enhancement of MHC-I-mediated antigen presentation, modulation of cytokine profiles, and promotion of pro-inflammatory macrophage polarization. Probiotics also regulate adaptive immunity via microbial metabolites such as short-chain fatty acids (SCFAs), inosine, and tryptophan derivatives that support effector T cell activation and reduce T cell exhaustion. Cross-reactivity between microbial and tumor-associated antigens (molecular mimicry) further underscores the potential of probiotic strains to stimulate antitumor responses. In these models, supplementation with specific bacterial strains such as Bifidobacterium spp., Lactobacillus spp., Clostridium butyricum, and Akkermansia muciniphila enhanced ICI responses across tumor types including melanoma, lung cancer, and colorectal cancer. These findings are in part supported by early-phase clinical studies and retrospective cohorts, particularly in lung and renal cancers, where probiotic use has been associated with improved progression-free and overall survival. However, most clinical data are observational, and the field lacks standardized probiotic formulations and dosing protocols. To transition probiotics from food supplements to clinically validated immunotherapy adjuncts, rigorous mechanistic, translational, and clinical studies are necessary. These approaches have the potential to define mechanism-of-action, identify immunologically active strains, and inform rational clinical trial design. With careful development, probiotics hold promise as cost-effective, scalable, and personalized tools to optimize the efficacy and safety of cancer immunotherapy.